2016
DOI: 10.1021/acs.biochem.5b01259
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Aβ1–40 and Aβ1–42 Peptides in Solution Adopt Very Similar Ramachandran Map Distributions That Closely Resemble Random Coil

Abstract: The pathogenesis of Alzheimer’s disease is characterized by the aggregation and fibrillation of amyloid peptides Aβ1–40 and Aβ1–42 into amyloid plaques. Despite strong potential therapeutic interest, the structural pathways associated with the conversion of monomeric Aβ peptides into oligomeric species remain largely unknown. In particular, the higher aggregation propensity and associated toxicity of Aβ1–42 compared to that of Aβ1–40 are poorly understood. To explore in detail the structural propensity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
219
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(255 citation statements)
references
References 99 publications
33
219
3
Order By: Relevance
“…19 These scalar couplings include 3 J HN–Ha , 3 J Ha–C′ , 3 J HN–C′ , and 3 J C′–C′ , which report on the phi dihedral angle, and 1 J N–C α and 2 J N–C α , which report on the ψ dihedral angle. As can be seen on Figure 10, and assuming an uncertainty of 5% in the experimental values, 17 the F99 and FOP 3 JHN-Ha constants along the sequence are very similar and clearly different from the F22 and F14 corresponding J -profiles, with the largest deviation involving the amino acid region 16–39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 These scalar couplings include 3 J HN–Ha , 3 J Ha–C′ , 3 J HN–C′ , and 3 J C′–C′ , which report on the phi dihedral angle, and 1 J N–C α and 2 J N–C α , which report on the ψ dihedral angle. As can be seen on Figure 10, and assuming an uncertainty of 5% in the experimental values, 17 the F99 and FOP 3 JHN-Ha constants along the sequence are very similar and clearly different from the F22 and F14 corresponding J -profiles, with the largest deviation involving the amino acid region 16–39.…”
Section: Discussionmentioning
confidence: 99%
“…12 Interestingly, on the basis of a complete set of chemical shifts and J couplings, the 34 N-terminal residues behave identically in the two monomeric species at pH 7, and the A β 40 and A β 42 ensembles resemble random coil, with the possibility of transient heterogeneous structured conformations of low probability. 19 …”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a β‐hairpin in the C‐terminus of A β42 could be the initial seed to start the aggregation process towards the β‐sheet rich amyloids . Recently, Roche et al . showed that A β42 monomers resemble A β40 and have no long‐range and only weak middle‐range NOE contacts and concluded that the peptides are mostly random coil.…”
Section: Discussionmentioning
confidence: 99%
“…Based on solution NMR analysis of Aβ 42 monomers that found no evidence of any residual secondary structure in this peptide14, Bax and colleagues recently proposed that early aggregation intermediates must be assembled via hydrophobically driven self-interactions of peptide segments in irregular structure. While our data on Aβ 42 concur that the first formed oligomers do not involve amyloid-like β-structure18 (Fig.…”
Section: Discussionmentioning
confidence: 99%